Efficacy of methyl ester of conjugated linoleic acid (t10, c12 isomer) for sows and cows for reproduction. (5th March 2019) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Durjava, Mojca Kos; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: A mixture of methylated conjugated linoleic acid (CLA) isomers (t10, c12 and c9, t11) in equal proportions is the subject of this assessment. The active substance is considered to be CLA (t10, c12) methyl ester (ME). The Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) of EFSA previously issued an opinion on the safety and efficacy of the product, in which it could not conclude on the efficacy of this additive for sows for reproduction and for cows for reproduction. The European Commission asked EFSA to deliver an opinion on the efficacy of this additive for sows and cows for reproduction, based on additional data submitted by the applicant. The FEEDAP Panel has performed the assessment of the new data following an approach in line with the principles laid down in Regulation (EC) No 429/2008 and the relevant guidance documents. In relation to the data on efficacy in sows for reproduction, owing to methodological shortcomings of the study submitted, including the duration of the study and the limited biological relevance of the effect observed, the FEEDAP Panel cannot conclude on the efficacy of CLA (t10, c12)‐ME for sows for reproduction. The data related to dairy cows indicate that dietary CLA (t10, c12)‐ME supplementation in the late dry period and/or lactation period showed an increase of the probability of pregnancy and a reduction of time to conception in the same reproductive cycle. However, considering that the minimum duration of efficacy studies for reproductive parameters is of at least two reproductive cycles, the FEEDAP Panel is not in a position to conclude on the efficacy of the additive for cows for reproduction.